(untitled) - Nickels, William G. (Boston, 2002)
Understanding Business by Nickels, McHugh, and McHugh has been the number one textbook in the introduction to business market for several editions for three reasons: (1) The commitment and dedication of an author team that teaches this course and believes in the importance and power of this learning experience, (2) we listen to our customers, and (3) the quality of our supplements package.
Keywords: Industrial management,Business,Business; Vocational guidance